Avaliação dos efeitos induzido pelo 2-nitrato-1,3-dibutoxipropano (NDBP) na função vascular em modelo de aterosclerose - Leite, Ericka Garcia (2019)
Atherosclerosis is a chronic arterial disease of inflammatory and fibroproliferative nature that affects thousands of people a year and is one of the leading causes of death worldwide. Endothelial dysfunction is one of the major detectable changes during the development of atherosclerosis. Characterized by impaired vasodilation and increased vasoconstrictor response, mainly by decreased NO bioavailability and loss of NO / GMPc / PKG signaling. Experimentally, it can be demonstrated by impaired endothelium-dependent relaxation of acetylcholine (Ach) and increased phenylephrine contraction response (Phe). Organic nitrates have been used for years to treat cardiovascular diseases mimicking the role of endogenous NO. However, long-term use of these compounds results in the development of tolerance. In this study an organic nitrate synthesized from glycerin, 2-nitrate-1,3-dibutoxypropane (NDBP) was evaluated. Thus, the aim of the present study was to evaluate the effects of NDBP on vascular function in an atherosclerosis model. Male mice from C57BL / 6 (CT) and apolipoprotein E (apoE-/-) knockouts were used, which respectively received standard diet and Western type atherogenic diet (Rhoster, São Paulo, Brazil), containing 41% of calories in the form of lipids and 1.5% cholesterol from 8 weeks of life over the next 12 weeks. The animals were separated into 3 groups: standard diet C57 control animals, atherogenic diet apoE-/- animals and atherogenic diet apoE-/- animals treated chronically with NDBP. Animal blood was collected for total cholesterol measurement. Animal aortas were collected and processed for organ bath studies or histological evaluation of plaque deposition (Oil-Red staining), ROS production (DHE) and NO (DAF-2DA). Vascular function was assessed by constructing ACh concentration-response curves (100 pM - 30 μM) after phenylephrine pre-contraction (PHE, 10 μM) and PHE concentration-response curves (100 pM - 30 μM). To assess endogenous NO production by indirect method, after pre-contraction with PHE (10μM) the rings were incubated with the non-specific nitric oxide synthase isoform inhibitor L-NAME (100 μM). In order to evaluate the influence of NDBP on vascular function, the rings were incubated with NDBP (10 μM) and vascular function tests were performed. The evaluation of NDBP vasorelaxant activity was performed by NDBP concentration-response curves (100 pM - 30 μM) after PHE pre-contraction (10 μM) in rings with and without endothelium. To assess whether the effect of NPBP on vascular function is dependent on NO or antioxidant activity, the rings were incubated with either NDBP (10μM) plus hydroxycobalamin (HDX, 100μM) or tempol (1μM). In the apoE-/- group that was chronically treated for 14 days, after treatment, vascular function test and baseline NO production were evaluated. The apoE-/- animals showed approximately 12-fold increase in cholesterol levels (TC 58.2 ± 3.6 vs. apoE-/- 704.9 ± 29.9) and marked plaque deposition (CT 0 ± 0 vs. apoE-/- 57 ± 4.9 ). The apoE-/- animals showed marked endothelial dysfunction with impaired ACh relaxation (CT Rmax: 76.7 ± 5.4 and pD2: 7.9 ± 0.3 vs. apoE-/- Rmax: 62.7 ± 5.5 and pD2: 6.7 ± 0.2) and higher response to PHE (CT Rmax: 51.1 ± 9.2 and pD2: 6.8 ± 0.06 vs. apoE-/- Rmax: 82.0 ± 8.3 and pD2: 6.8 ± 0.07). By indirect method, basal NO production was decreased in these animals, demonstrated by the decrease in delta contraction after L-NAME blockade (CT 0.46 ± 0.04 and 45.3 ± 4.1% vs. apoE-/- 0.30 ± 0.01 and 33.2 ± 1.9 %). The same was observed by the direct method using DAF-2DA: apoE-/- animals showed decrease in NO production (CT 131855 ± 15774 vs. apoE-/- 84057 ± 13397). Decreased NO production in apoE-/- animals was reversed following acute NDBP treatment, demonstrated by increased NO concentration measured by DAF-2DA in both groups (CT 196357 ± 18312 vs. apoE-/- 223507 ± 6996). Using the DHE probe it was observed that the apoE-/- animals showed increase in the production of ROS (CT 114036 ± 15280 vs. apoE-/- 166649 ± 13022) and after incubation with NDBP ROS production was decreased in these animals (136043 ± 8281).. NDBP promoted vascular relaxation to the same extent in both groups with absence of endothelium (apoE-/- Rmax: 93 ± 4.1 and pD2: 5.8 ± 0.3; CT Rmax: 102 ± 9.6 and pD2: 5.6 ± 0.4), however in the presence of endothelium apoE-/- animals showed higher sensitivity to the compost (Rmax: 76 ± 11.3 and pD2: 7.2 ± 0.4) when compared to control (Rmax: 69 ± 6.7; pD2: 7.3 ± 0.4). Acute NDBP treatment reversed the ACh relaxation impairment observed in apoE-/- animals (79.4 ± 3.9; pD2: 8.2 ± 0.4) when compared to control (Rmax: 76.0 ± 3.7 pD 2: 7.9 ± 0.2). NDBP-induced vascular function improvement was abolished after joint incubation with HDX (Rmax: 59.9 ± 7.1 and pD2: 6.6 ± 0.3). NDBP-induced relaxation in apoE-/- endothelium-free animal (Rmax: 93 ± 4.1; pD2: 5.8 ± 0.3) was abolished after HDX pre-incubation (Rmax: 0.5 ± 0 6.6, pD2: 6.8 ± 0.9). In order to assess whether NDBP has antioxidant activity, tempol (SOD mimetic) was pre-incubated with or without NDBP. Tempol pre-incubated with NDBP has no potentiated effect (Rmax: 65.1 ± 7.3) when compared to tempol without NDBP (Rmax: 67.4 ± 9.5). ApoE-/- animals treated chronically with NDBP (40mg / kg / in) showed reversal in endothelial dysfunction, demonstrated by an improved relaxation response to ACh when compared to untreated apoE-/- animals (Rmax: 87, 4 ± 3.1; pD2: 7.8 ± 0.1 vs. Rmax: 62.7 ± 5.5; pD2: 6.7 ± 0.2 respectively), equating to the control animals (Rmax: 76.7 ± 5.4; pD2: 7.9 ± 0.3). They also showed an increase in basal NO production demonstrated by the increase in delta contraction when compared to untreated apoE-/- (Δ: 0.39 ± 0.2 vs. Δ: 0.30 ± 0.01 respectively). Thus, it can be concluded that NDBP has beneficial effects on experimental atherosclerosis, being able to reverse endothelial dysfunction by increasing NO bioavailability and its antioxidant effect.